2006
DOI: 10.2755/jcmm010.003.16
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of carbon monoxide in transplantation

Abstract: During the last decades due to the development of new immunosuppressive agents and improvements in organ preservation methods, surgical techniques, and postoperative care, organ transplantation has become an ultimate therapeutic option for irreversible organ failure. Early graft survival has significantly improved; however, the long-term outcome remains unsatisfactory. Multiple factors, both immunogenic and non-immunogenic etiologies, are involved in the deterioration of the allografts, and the recent use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 120 publications
2
43
0
Order By: Relevance
“…Thus, the initial loss of microvessels/peritubular capillaries may be a primary factor in the development of fibrosis and chronic renal disease (Kang et al, 2002; Reinders and Briscoe, 2002; Contreras and Briscoe, 2007; Mayer, 2011). Pharmacologic therapy which can protect microvascular integrity at early times post transplantation has potential to improve long-term graft survival (Johnson et al, 2006; Nakao et al, 2006; Aydin et al, 2007; Rabelink et al, 2007; Briscoe and Pal, 2008; Leonard et al, 2008; Hanto et al, 2010). If early protection and repair is not accomplished, then ongoing local ischemia will result in cellular atrophy, and chronic allograft disease will be inevitable.…”
Section: General Overviewmentioning
confidence: 99%
“…Thus, the initial loss of microvessels/peritubular capillaries may be a primary factor in the development of fibrosis and chronic renal disease (Kang et al, 2002; Reinders and Briscoe, 2002; Contreras and Briscoe, 2007; Mayer, 2011). Pharmacologic therapy which can protect microvascular integrity at early times post transplantation has potential to improve long-term graft survival (Johnson et al, 2006; Nakao et al, 2006; Aydin et al, 2007; Rabelink et al, 2007; Briscoe and Pal, 2008; Leonard et al, 2008; Hanto et al, 2010). If early protection and repair is not accomplished, then ongoing local ischemia will result in cellular atrophy, and chronic allograft disease will be inevitable.…”
Section: General Overviewmentioning
confidence: 99%
“…Of the metabolites generated by HO-1 catalysis, biliverdin (and bilirubin) has been shown to possess antioxidant activity, while carbon monoxide has been found to exert many salutary effects in various settings including myocardial ischemia 7, 11, 12. Although induction of HO-1 is known to constitute a common adaptive response that increases cellular resistance to oxidative injury and other types of injury 7, 12, 13, the role of HO-1 in the cardioprotection afforded by iNOS gene therapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This salutary property of CO was shown in 1999 in a landmark study that demonstrated that CO, at relatively low concentrations (50–500 parts per million), protected against hyperoxia-induced lung injury by suppressing inflammation and apoptosis 6. These findings presaged a groundswell of investigations demonstrating the beneficial effects of CO (when present in such low concentrations) in diverse models of tissue injury, and which reflected, depending on the disease model, any one or combination of the following properties of CO: antiapoptotic, anti-inflammatory, immune-suppressant, antithrombotic, angiogenic, antifibrotic, and vasorelaxant 2–4,7,8. Moreover, such protection was conferred not only by CO administered as a gas but also by novel CO-releasing compounds 3…”
mentioning
confidence: 91%
“…The cytoprotective properties of HO-1 were rapidly explored in the field of transplantation and were observed to mitigate ischemia/reperfusion injury of the transplanted kidney, acute renal allograft rejection, and chronic allograft nephropathy; these protective effects were recapitulated, in part, by products of HO such as CO and/or bile pigments 7,8. Attention was also directed to organ preservation, an issue of central importance in this field, and one renewed by the increasing use of marginal donor organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation